Analisis Beban Pencemaran terhadap Tekanan Ekologis Perairan Sungai Sringin Kota Semarang Jawa Tengah - Rifandi, Raditya; Abdillah, Rangga Fajar; Falakh, Fajrul; Fahmi, Dafa Anwarul (Fakultas Ilmu dan Teknologi Hayati Universitas Teknologi Sumbawa, 2026)
This study evaluates pollution load, water quality status, biodegradability characteristics, and ecological pressure in the Sringin River, Semarang City, Central Java. Key parameters analyzed included Total Suspended Solids (TSS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and lead (Pb), supported by measurements of discharge, pH, temperature, dissolved oxygen (DO), and salinity using purposive sampling across three river segments. The results show increasing pollution from upstream to downstream, with BOD ranging from 6.2 to 12.2 mg/L, COD from 302 to 327 mg/L, TSS up to 151 mg/L, and Pb concentrations reaching 7.31 mg/L—far exceeding the quality standard of 0.03 mg/L. Dissolved oxygen remained above 7 mg/L but exhibited spatial fluctuation, while the BOD/COD ratio (< 0.3–0.4) indicates the dominance of partially non-biodegradable waste that slows natural self-purification. Pb accumulation in water, sediments, and aquatic biota suggests potential ecological and human health risks through bioaccumulation and biomagnification. Overall, the Sringin River experiences chronic ecological pressure due to combined organic and inorganic pollution, emphasizing the need for source-based pollution control, continuous monitoring, and ecological risk–oriented water quality management to sustain aquatic ecosystem functions.